Bandwidth Optimization of Single-walled Carbon Nanotube Dipole Antenna at GHz Frequency Regime - N. Jurn, Yaseen (International Journal of Advanced Engineering, Management and Science, 2022)
This paper presents two different materials-based carbon nanotube composite (CNT-composite) material for antenna applications. These materials are single-walled CNT SWCNT and single-walled CNT composite material SWCNT-composite. The SWCNT are coated by a thin layer of (graphite, silver, or copper) material to construct new Nano-materials. Scientific and mathematical modeling approaches are presented in order to estimate the electromagnetic properties of these materials into CST (MWS) software package. For the purpose of supporting these modeling approaches, the required mathematical analysis is presented and discussed. The dipole antenna configuration will be utilized to estimate the electromagnetic properties of the SWCNT-composite a material. The results of this work showed the enhancement in the electromagnetic properties of the SWCNT-composite materials compared with the SWCNT material, respectively. The bandwidth and fractional bandwidth are the main enhance parameters that will be focused in this work.